Ultrawide band CBCPW to stripline vertical transition in multilayer LCP substrates. Issue 6 (June 2015) - Zhang, Yifei; Shi, Shouyuan; Martin, Richard D.; Prather, Dennis W.
ABSTRACT: This article presents an improved design of conductor‐backed coplanar waveguide (CBCPW)‐to‐stripline (SL) vertical transition in multilayer liquid crystal polymer substrates. The CBCPW and SL is designed on the top and second conductor layers, respectively, and electrically connected with each other through micro‐vias. The reported transition is optimized using High Frequency Simulation Software, and the simulated results predict low loss over an ultrawide bandwidth. To validate our design, a CBCPW‐to‐SL‐to‐CBCPW transition was fabricated and characterized. The back‐to‐back transition shows an insertion loss of less than 2.5 dB and a return loss of less than −10 dB over a frequency band from DC to 78 GHz. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1481–1484, 2015